Study of Performance of Real Time Streaming Protocol (RTSP) in Learning Systems - Watequlis Syaifudin, Yan; Fahrur Rozi, Imam; Ariyanto, Rudy; Rohadi, Erfan; Adhisuwignjo, Supriatna (International Journal of Engineering and Technology, 2018)
Education is a very important aspect to develop the country to become more advanced. However, the constraints such as lack of education budgets have restricted many schools to invest in learning support equipment. One of the technologies in multimedia that can be used to build a learning system is media streaming that use a standard of implemented protocol is Real Time Streaming Protocol (RTSP). It can be used to build media streaming based learning model. This research will explain about the performance of RTSP if implemented in a classroom learning with capacity up to 50 hosts. Measurement is based on the performance aspect of the streaming process, including latency time, streaming lag, and CPU utilization. Parameters used to compare performance are media type, media format, media size, media quality, and number of clients. The combination of each parameter will produce different value of performance aspects. As a case study, foreign language subject is a learning activity that requires multimedia communication including video and audio, then this requirement can be solved with the development of media streaming based software using the RTSP. In the end it can be concluded about the feasibility of using RTSP to develop the learning system.Â Â Â